Sarcopenic obesity in predialysis chronic kidney disease: Muscle strength is a predictor of mortality and disease progression in a six-year prospective cohort - Dílmerson Oliveira; Viviane Angelina de Souza; Guilherme Cardenaz Souza; Lucas Fernandes Suassuna; Marcus Gomes Bastos; Maycon Moura Reboredo; Natália Maria da Silva Fernandes (PLoS ONE, 2025)
Introduction Sarcopenic obesity (SO) is a poorly defined physiological condition that is associated with increased morbimortality in the general population. The prevalence of SO has increased, making it an important public health issue; however, its effects when associated with other chronic conditions are still unclear. Therefore, it is necessary to comprehend the potential outcomes in chronic kidney disease (CKD) patients. Objective To assess the associations of predialysis CKD patients with SO and its components with death and disease progression to renal replacement therapy (RRT). Methods Prospective six-year cohort with 100 patients with predialysis CKD (stages one through five). Participants were older than 18 years and signed an informed consent form. The data were collected in an outpatient clinic specializing in predialysis care, and demographic, clinical, laboratory and inflammatory variable data were collected. A descriptive analysis was performed, and the SO and non-SO groups were compared with Student’s t test, Mann‒Whitney U test and Cox regression, taking into consideration all relevant confounding variables. Body composition variables utilized to diagnose SO were separately analyzed along with the outcomes. Results Sixteen percent of our sample were diagnosed with SO, but this was not associated with death or RRT, while lower BMI values were negatively associated with these outcomes. However, in an isolated analysis, handgrip strength was correlated with both RRT (p = 0.029) and death (p = 0.003). We recommend that health professionals pay greater attention to muscle strength, striving for earlier assessment, in an effort to better counsel patients and implement actions to increase or preserve strength through nonpharmacological treatment, such as resistance training.